Two to tango? Psychological contract breach in online labor markets - Jörg Claussen; Tobias Kretschmer; Pooyan Khashabi; Mareike Seifried (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Despite some advantages over traditional (offline) labor markets - such as lower search costs, better matching and improved monitoring - online labor markets (OLMs) have not taken off as initially expected. In this paper, we study the factors that limit perceived project success on OLMs. Using psychological contract theory, we theorize how common OLM features including contracts with virtual monitoring, multi-freelancer projects, and simultaneous projects by a client trigger the perception of psychological contract breach among OLM participants and reduce perceived project success for both participants. We test these hypotheses using an extensive dataset with more than 143,000 transactions on the world's largest freelancing platform, Upwork, and find that - contrary to predictions from agency theory - projects equipped with strict freelancer monitoring (hourly-pay contracts) and projects enabling peer comparison (multi-freelancer projects or multiple simultaneous projects), lead to lower perceived project success both from the freelancer's and the client's perspective. Our work implies that transactions on online labor markets should not be viewed solely as agency relations, and that some features that supposedly reduce agency costs and improve efficiency on OLMs come at the cost of triggering the perception of psychological contract breach.
Keywords: L14; L24; J44; 330; Online labor markets; gig economy; outsourcing; psychological contract theory; platforms; knowledge work